Technology gap ratio decomposition in sugarcane farming in Indonesia - AR, Nuhfil Hanani; Asmara, Rosihan; Fahriyah, Fahriyah (Asian Journal of Agriculture and Rural Development, 2023)
Indonesia’s population and income growth have led to a higher demand for raw sugar and its derivative products; for this reason, sugarcane production must be improved, especially in central production areas. However, efforts are constrained by the disparity in resource endowment and technology. This study aimed to analyse technical, technological, and managerial gaps in sugarcane farming in different areas of East Java. The study used primary data collected through a survey during the 2019/2020 sugarcane planting season in Malang, Kediri, and Mojokerto Regencies. A structured questionnaire was used to collect data on inputs and outputs. A meta-frontier data envelopment analysis (meta-DEA) approach was used to measure the technical efficiency of sugarcane farming in each research area. The decomposition using meta-DEA showed that, on average, the meta-technical inefficiency of sugarcane farmers was caused mainly by managerial gaps, as the average managerial gap inefficiency (MGI) was more significant than the technological gap inefficiency (TGI). Malang regency showed the largest TGI and MGI, indicating that sugarcane farmers in Malang regency have lower managerial skills for decision-making and a lower level of production technology compared to the other two regions. Based on the findings of this study, the government should improve technological innovation to mitigate the technology gap that was found in our research location.